If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7+(-5b)=-23
We move all terms to the left:
7+(-5b)-(-23)=0
We add all the numbers together, and all the variables
(-5b)+30=0
We get rid of parentheses
-5b+30=0
We move all terms containing b to the left, all other terms to the right
-5b=-30
b=-30/-5
b=+6
| 3x/5-0,5=1,9 | | 2x(5x-13)=-12 | | x/4+7=-8 | | 93=-3-2(-5x-8) | | 8x+6-7x=10 | | 22x+6=3x-2 | | 18x+6=3x-2 | | x3+3=576 | | 3x-5(x-3)=-8+5x+2 | | x=13+2/3 | | x/36=-18+25 | | 0=12x^2-48x+32 | | -7x^2+18x-8=0 | | 6s+30-30=180-30 | | 10x-82/3=8x | | (x-2)(x+1)=(x-2)(x+2) | | 55=10-x | | -5(-2+3v)=-110 | | 4(2x+6)−6(2x−8)=11x+3(5x−8) | | -15=-7+w/2 | | 21=7z-13z-21 | | 100-40x=0 | | 4v+4=12 | | 33.p=3;p=11 | | 2(u=6)-5u | | -246=-6(6+7r) | | 100-30x=0 | | 20x-5+45+40=180 | | 100-10x=0 | | 75=0.5(x-30) | | (x+1)(x+2)=(x-4)(x+5) | | 3(2x-4)=9-3(x-1) |